APUNTES TEÓRICO-METODOLÓGICOS PARA UN ESTUDIO DE LA MENSAJERÍA INSTANTÁNEA DESDE LAS CIENCIAS SOCIALES Y LAS HUMANIDADES - Dra. Rosalba MANCINAS-CHÁVEZ,Dr. Ramón REIG (Fonseca, Journal of Communication, 2023)
This article defends the need for transversality when methodologically addressing instant messaging via cellphones as a tool of communication from the point of view of social sciences and humanities. This leads us to the structural approach, which requires supplementary knowledge in fields such as Psychology or History, without losing sight that our study is composed in the areas of Communications and Journalism